Liderazgo ético vs. liderazgo de servicio: convergencias, tensiones e impacto en la creatividad individual (2020-2025) - Santiago-Torner, Carlos (Revista Galega de Economía, 2026)
Este artículo reflexiona críticamente sobre el impacto del liderazgo ético y del liderazgo de servicio en la creatividad individual en contextos organizacionales entre 2020 y 2025. A partir de una revisión sistemática y argumentativa de literatura reciente, se analizan sus convergencias, divergencias y efectos diferenciados sobre las condiciones psicosociales que facilitan o inhiben la generación de ideas novedosas. Aunque ambos estilos comparten una raíz ética y relacional, sus mecanismos de influencia difieren y pueden potenciar o limitar la creatividad según su intensidad moral, orientación normativa o el grado de contención emocional. El análisis revela además dinámicas paradójicas y zonas de sombra que cuestionan la visión idealizada del liderazgo prosocial como motor automático de innovación. Como aporte conceptual, el estudio introduce el modelo emergente de liderazgo prosocial-creativo, una propuesta interpretativa que integra principios éticos, sensibilidad relacional y condiciones psicológicas favorables para la creatividad. El trabajo concluye con implicaciones teóricas y prácticas orientadas a promover entornos donde ética y creatividad se potencien de manera mutua y contextualizada.
Ethical leadership vs. servant leadership: convergences, tensions, and impact on individual creativity (2020-2025)
This article offers a critical reflection on the impact of ethical leadership and servant leadership on individual creativity in organizational contexts between 2020 and 2025. Drawing on a systematic and argumentative review of recent literature, it examines the convergences, divergences, and differentiated effects of these prosocial leadership styles on the psychosocial conditions that facilitate or hinder the generation of novel ideas. Although both styles share an ethical and relational foundation, their mechanisms of influence differ and may either foster or limit creativity depending on their moral intensity, normative orientation, and degree of emotional containment. The analysis also reveals paradoxical dynamics and shadow areas that challenge idealized views of prosocial leadership as an automatic driver of innovation. As a conceptual contribution, the study introduces the emerging model of prosocial–creative leadership, an interpretive proposal that integrates ethical principles, relational sensitivity, and psychological conditions conducive to creativity. The article concludes with theoretical and practical implications aimed at promoting organizational environments in which ethics and creativity mutually reinforce each other in a contextualized manner.
Keywords: liderazgo ético; liderazgo de servicio; creatividad individual; moralidad organizacional; reflexión crítica; ethical leadership; servant leadership; individual creativity; organizational morality; critical reflection